PENDIDIKAN KARAKTER DALAM PEMBELAJARAN DARING DAN LURING: STUDI KASUS DI SD NEGERI 01 BUANTAN LESTARI - Nurul Sapitri; Dzikri, Ahludz; Atun Anis, Mifta; Jaya Adi Putra, M.; Dwisantoso, Ridwan (PGRI Provinsi Riau, 2021)
It aims to know character education in both online and offline learning. The method used was with qualitative research and with a qualitative approach. A data-gathering technique using closed interviews. Research is carried out at zero-one country elementary school. Data obtained through methods of observation, interview and documentation. Based on the results of research, conclusions can be drawn: (1) character analyses in online and offline learning are well under way and have already been applied to all students; (2) on this study the teacher has been enthusiastic about adding character values to the students who begin with the first class to attach themselves; (3) of the 11 aspects available, it can be seen that teachers already embed character values from the RPP design, to application of learning materials.